MSCs Modified With ACE2 Restore Endothelial Function Following LPS Challenge by Inhibiting the Activation of RAS. Issue 3 (March 2015) - He, Hong‐li; Liu, Ling; Chen, Qi‐hong; Cai, Shi‐xia; Han, Ji‐bin; Hu, Shu‐ling; Chun, Pan; Yang, Yi; Guo, Feng‐mei; Huang, Ying‐zi; Qiu, Hai‐bo
<x xml:space="preserve">Abstract</x> Angiotensin (Ang) II plays an important role in the process of endothelial dysfunction in acute lung injury (ALI) and is degraded by angiotensin‐converting enzyme2 (ACE2). However, treatments that target ACE2 to injured endothelium and promote endothelial repair of ALI are lacking. Mesenchymal stem cells (MSCs) are capable of homing to the injured site and delivering a protective gene. Our study aimed to evaluate the effects of genetically modified MSCs, which overexpress the ACE2 protein in a sustained manner via a lentiviral vector, on Ang II production in endothelium and in vitro repair of lipopolysaccharide (LPS)‐induced endothelial injury. We found that the efficiency of lentiviral vector transduction of MSCs was as high as 97.8% and was well maintained over 30 passages. MSCs modified with ACE2 showed a sustained high expression of ACE2 mRNA and protein. The modified MSCs secreted soluble ACE2 protein into the culture medium, which reduced the concentration of Ang II and increased the production of Ang 1–7. MSCs modified with ACE2 were more effective at restoring endothelial function than were unmodified MSCs, as shown by the enhanced survival of endothelial cells; the downregulated production of inflammatory mediators, including ICAM‐1, VCAM‐1, TNF‐α, and IL‐6; reduced paracellular permeability; and increased expression of VE‐cadherin. These data demonstrate that MSCs modified to overexpress the ACE2 gene can produce biologically active ACE2 protein over a sustained period of time and have an enhanced ability to promote endothelial repair after LPS challenge. These results encourage further testing of the beneficial effects of ACE2‐modified MSCs in an ALI animal model. J. Cell. Physiol. 230: 691–701, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company